(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
Pasture poisoning is a common cause of death in cattle and represents significant economic losses to the cattle industry in Argentina. Senna occidentalis intoxication has a high mortality - sometimes up to 100% mortality rate - and causes an acute to chronic disease. The season of the year, phenological stage of the plant and the feeding system used need to be considered before letting the cattle graze in a pasture with S. occidentalis. Cows usually eat the plant if present in the pasture or accidentally mixed with their feed. Affected animals can show progressive weakness, be found laterally recumbent, and display myoglobinuria. The central nervous system is unaffected. On necropsy, multiple necrotic foci can be found on the liver and myocardium, along with myodegeneration of the hindlimb muscles. Diagnosis of intoxication is confirmed with serum biochemistry and histopathology.